Meisoindigo Acts as a Molecular Glue to Target PKMYT1 for Degradation in Chronic Myeloid Leukemia Therapy - Zhao‐Xin Zhang; Shu‐Ying Li; Fang‐Fei Li; Qin‐Yan Shi; Cheng‐Yong Tan; Xiao‐Jing Wang; Mi Li; Yun‐Bao Liu; Jing Jin; Yong Li; Shi‐Shan Yu (Advanced Science)
Abstract Meisoindigo (Mei) has been clinically utilized for the treatment of chronic myeloid leukemia (CML), yet the precise molecular targets by which it exerts effects remain unclear. Through activity‐based protein profiling (ABPP), the protein kinase, membrane‐associated tyrosine/threonine 1 (PKMYT1) is identified as a direct target of Mei. Specifically, Mei forms a selective and reversible covalent bond with the Cys301 residue of PKMYT1, triggering its K48‐linked polyubiquitination and accelerating proteasomal degradation, which is mediated by the E3 ligase TRIM25. The study reveals that Mei acts as a molecular glue, enhancing the interaction between PKMYT1 and TRIM25 by approximately 30‐fold, thereby facilitating efficient PKMYT1 degradation. Further investigations reveal the pivotal role of PKMYT1 in cell growth. Knockdown of PKMYT1 in K562 cells induces G2/M phase arrest, enhances early apoptosis, and inhibits cell proliferation. In an orthotopic xenograft model, PKMYT1 knockdown delays leukemia progression and reduces lymph node metastasis, reinforcing its role in CML progression and metastasis. These findings provide a molecular rationale for the clinical efficacy of Mei and highlight PKMYT1 as a promising therapeutic target for CML. Additionally, it offers a valuable scaffold and inspiration for the development of novel molecular glue‐based protein degraders.